THE EFFECT OF DETERMINATION MICRONUTRIENT CONCENTRATION ON THE FORMATION OF BIOETHANOL IN THE PROCESSING OF THE PALM OIL MILL EFFLUENT - Ilham Anggamulia, Muh.
Biomass is a central issue as a new material that can be used as a substrate to be converted into biofuel to replace renewable and sustainable liquid fossil fuels. Palm oil mill effluent (POME) is the potential of Agri-industrial waste as an alternative energy by processing using anaerobic processes to set aside its organic content as well as to produce products, such as alcohol compounds, volatile acids, methane gas, and others. This research will be carried out as a study of the effect concentration variations of Fe2+, Mo2+, and Ni2+ micronutrients on the formation of bioethanol and acidogenic by products in anaerobic conditions. Circulating Bed Reactor (CBR) is used as a reactor that is operated for 48 hours in batch. The control variations in this study resulted in a bioethanol concentration of 108.64 mg/L. Concentrations for the addition of three micronutrients were 191.44 mg / L produced by the combination of Fe2+ 1 mg / L, Ni2+ 1 mg / L, Mo2+ 0.6 mg / L. The combination of the three micronutrients was able to produce a concentration of bioethanol almost twice greater than the variation of control by increasing the bioethanol yield by 39.1% and the degree of ethanofication (DE) by 0.048. The distribution of products produced when the maximum bioethanol concentration is 4.74% bioethanol; 5.18% acetate; 46.87% butyrate; 9.68% propionate; and 0.92% valerate. The formation of volatile acids produced a degree of acidification (DA) of 0.005. DE value smaller than DA can indicate a shift in the product towards the formation of bioethanol.